Omental adipose tissue gene expression, gene variants, branched-chain amino acids, and their relationship with metabolic syndrome and insulin resistance in humans - Serralde-Zúñiga, Aurora E; Guevara-Cruz, Martha; Tovar, Armando R; Herrera-Hernández, Miguel F; Noriega, Lilia G; Granados, Omar; Torres, Nimbe (Genes & nutrition, 2014)
Obesity is a complex disorder caused by several factors. Thus, the aim of the present study was to assess whether the expression of genes in the omental white adipose tissue (AT) of subjects with insulin resistance (IR) or metabolic syndrome (MetS) is associated with an elevation in serum branched-chain amino acids (BCAAs) and whether this response depends on specific genetic variants. Serum BCAA concentration, the adipocyte area, and gene variants of PPARγ, ABCA1, FTO, TCF7L2, GFOD2, BCAT2, and BCKDH were determined in 115 Mexican subjects. The gene expression in the AT and adipocytes of BCAT, BCKDH E1α, C/EBPα, PPARγ2, SREBP-1, PPARα, UCP1, leptin receptor, leptin, adiponectin, and TNFα was measured in 51 subjects. Subjects with IR showed higher values for the BMI, HOMA-IR, and adipocyte area and higher levels of serum glucose, insulin, leptin, and C-reactive protein, as well as an elevation of the AT gene expression of SREBP-1, leptin, and TNFα and a significant reduction in the expression of adiponectin, BCAT2, and BCKDH E1α, compared with non-IR subjects. The presence of MetS was associated with higher HOMA-IR as well as higher serum BCAA concentrations. Subjects with the genetic variants for BCAT2 and BCKDH E1 α showed a lower serum BCAA concentration, and those with the ABCA1 and FTO gene variant showed higher levels of insulin and HOMA-IR than non-IR subjects. AT dysfunction is the result of a combination of the presence of some genetic variants, altered AT gene expression, the presence of MetS risk factors, IR, and serum BCAA concentrations.